THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN PESANTREN, MADRASAH, AND SCHOOLS IN THE MILLENNIAL ERA - Wahyuni, Ana Dwi; Khabibul Umam , Mustolikh; Delimanugari, Daluti; Solicah, Nisa Munadatus; Ardhelia, Serli (STAI Asy-Syukriyyah, 2024)
The purpose of this study is to determine how the PAI curriculum is developed in pesantren, madrasah, and schools in the millennial era. This study uses a qualitative approach with a library research approach. The research results show that the curriculum is an essential component of the education program because it functions as a system and as a tool to achieve educational goals. In curriculum development, it must be adjusted to the conditions of students, schools, and the surrounding socio-cultural community, other parties related to the school. That is relevant to the needs and characteristics of the millennial generation will help them become individuals who are faithful, pious, and have noble character, which can be developed through intracurricular and extracurricular activities. Madrasah and pesantren prioritize in-depth Islamic education, while schools focus on general education in their curriculum development.